The Logic of Gift and Gratuitousness in Business Relationships - Faldetta, Guglielmo (2011)
The logic of gift and gratuitousness in business activity raised by the encyclical Caritas in Veritate stresses a deeper critical evaluation of the category of relation. The logic of gift in business includes two aspects. The first is considering the logic of gift as a new conceptual lens in order to view business relationship beyond contractual logic. In this view, it is crucial to see the circulation of goods as instrumental for the development of relationships. The second aspect is to qualify the relationships established through the gift, and to think about the motivation in gift-giving, which has an ethical content. We give because we have received, and through gift-giving we develop relationships that have a high ‘bonding value’. Analysing the logic of gift in business management may permit us to gain an understanding of the ambiguity of gift-giving in organizations. Looking at the relationships between organizations and employees, and organizations and customers, we can discover why the logic of gift is often misunderstood or abused in its application, and how it should be applied to be more consistent with the message of Caritas in Veritate.
Keywords: Organizations; Logic of gift; Gratuitousness; Catholic Social Teaching; Caritas in Veritate; Business relationships; Business Management; Benedict XVI